Baseline Characteristics of the Korean Registry of Pulmonary Arterial Hypertension - Wook-Jin, Chung; Yong Bum, Park; Chan Hong, Jeon; Jo Won, Jung; Kwang-Phil, Ko; Sung Jae, Choi; Hye Sun, Seo; Jae Seung, Lee; Hae Ok, Jung; Moo Suk, Park (Journal of Korean Medical Science, 2015)
Despite recent advances in understanding of the pathobiology and targeted treatments of pulmonary arterial hypertension (PAH), epidemiologic data from large populations have been limited to western countries. The aim of the Korean Registry of Pulmonary Arterial Hypertension (KORPAH) was to examine the epidemiology and prognosis of Korean patients with PAH. KORPAH was designed as a nationwide, multicenter, prospective data collection using an internet webserver from September 2008 to December 2011. A total of 625 patients were enrolled. The patients' mean age was 47.6 ± 15.7 yr, and 503 (80.5%) were women. The diagnostic methods included right heart catheterization (n = 249, 39.8%) and Doppler echocardiography (n = 376, 60.2%). The etiologies, in order of frequency, were connective tissue disease (CTD), congenital heart disease, and idiopathic PAH (IPAH) (49.8%, 25.4%, and 23.2%, respectively). Patients with WHO functional class III or IV at diagnosis were 43.4%. In total, 380 (60.8%) patients received a single PAH-specific treatment at the time of enrollment, but only 72 (18.9%) patients received combination therapy. Incident cases during the registry represented 297 patients; therefore, the incidence rate of PAH was 1.9 patients/yr/million people. The 1st-, 2nd-, and 3rd-yr estimated survival rates were 90.8%, 87.8%, and 84.4%, respectively. Although Korean PAH patients exhibited similar age, gender, and survival rate compared with western registries, they showed relatively more CTD-PAH in the etiology and also systemic lupus erythematosus among CTD-PAH. The data suggest that earlier diagnosis and more specialized therapies should be needed to improve the survival of PAH patients.